The Unemployment Insurance Taxable Wage Base Mystery - Donald O. Parsons (Institute of Labor Economics (IZA), 2017)
Unemployment insurance experts lament the low Federal taxable wage base (TWB), last increased to 7000 per worker in 1982. The Federal TWB sets only a system minimum and by 2014 all but two states had TWBs that exceeded the minimum, opening up state TWB choice for study. States do align TWB with state payroll earnings. Indeed TWB/WAGE ratios within states have been remarkably stable for decades, though the ratio varies dramatically across states. Critics seem especially concerned about the tax regressivity of low TWBs, but the hypothesis that more progressive states choose less regressive (higher) TWBs is flatly rejected by the data. Earlier UI analysts focused on employer insurance equity, and the resistance of low cost, high-wage (stable) employers to subsidizing high cost, low-wage (unstable) employers. These analysts provided convincing evidence that (i) employers believed this to be the key issue, and (ii) the TWB did redistribute the insurance premium burden in the hypothesized direction. Across states – wage levels constant – economies characterized by greater income inequality and a preponderance of large (low turnover) firms are associated with lower TWBs. Apparently critics were right to imagine a link between wages and the TWB, but ignored the fact that this matching could be done better across location.
Keywords: J65; J41; J33; 330; unemployment insurance; taxable wage base; experience rating